Electric motors AC motor controllers 2 - Primedia Workplace Learning ([United States] : PRIMEDIA Workplace Learning)
This interactive training unit is designed to familiarize trainees with basic procedures for troubleshooting and maintaining AC motor controllers. After completing this unit, trainees should be able to use diagrams and charts to obtain information about an AC motor controller. They should also be able to explain how to troubleshoot a problem in an AC motor controller and how to inspect and clean a controller's parts.
Keywords: Electric motors; Electric controllers